2017
DOI: 10.1038/s41598-017-12099-8
|View full text |Cite
|
Sign up to set email alerts
|

Flexible polarimetric probe for 3 × 3 Mueller matrix measurements of biological tissue

Abstract: Polarimetry is a noninvasive method that uses polarised light to assess biophysical characteristics of tissues. A series of incident polarisation states illuminates a biological sample, and analysis of sample-altered polarisation states enables polarimetric tissue assessment. The resultant information can, for example, help quantitatively differentiate healthy from pathologic tissue. However, most bio-polarimetric assessments are performed using free-space optics with bulky optical components. Extension to fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…The primary polarization properties of a sample are the depolarization, retardance—including linear‐ and circular‐retardance—and diattenuation . These properties—especially depolarization and linear‐retardance—have been used to investigate biological tissue microstructure and composition, and could benefit tissue diagnosis and image‐guided therapy . It has been reported that tissue linear‐retardance contributes to partial bladder obstruction assessment , nonstaining microscopy for liver fibrosis and cervical cancer diagnosis , characterization of radiofrequency ablation extent in myocardium and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The primary polarization properties of a sample are the depolarization, retardance—including linear‐ and circular‐retardance—and diattenuation . These properties—especially depolarization and linear‐retardance—have been used to investigate biological tissue microstructure and composition, and could benefit tissue diagnosis and image‐guided therapy . It has been reported that tissue linear‐retardance contributes to partial bladder obstruction assessment , nonstaining microscopy for liver fibrosis and cervical cancer diagnosis , characterization of radiofrequency ablation extent in myocardium and so on.…”
Section: Introductionmentioning
confidence: 99%
“…This paper will introduce Mueller polarimetry as a novel optical diagnostic technique that allows monitoring of the surface evolution of the targeted material while characterizing the interaction by capturing images of the induced electric field due to deposited surface charges. This technique has been used in the past for the examination of various tissues [4][5][6] , however it has never been used for tissues in-situ during direct plasma exposure as we show in this work. A diagnostic with that capability would be very useful since different types of samples and various plasma devices/exposures can be investigated and compared through the induced electric field.…”
mentioning
confidence: 99%
“…[26][27][28][29] Therefore, MMIP is becoming increasingly attractive for distinguishing the structural features of biological tissue in food quality control and medical diagnostics. 18,24,28,[30][31][32][33][34][35][36][37] Optical characterization of biological tissue within the framework of the Stokes-Mueller formalism is based on measuring the bulk tissue's polarimetric transfer function, known as its Mueller matrix. This information-rich tissue signature includes the full polarization information reflecting its biophysical properties.…”
Section: Mueller Matrix Polarimetrymentioning
confidence: 99%